Ethanol Production from Non-Food Tubers of Iles-iles (Amorphophallus campanulatus) by Using Separated Hydrolysis and Fermentation - Kusmiyati Kusmiyati (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
The decrease in production and the raise in needs have led to the rise in oil prices. This work investigated the possibility of Iles-iles (Amorphophallus campanulatus) tuber flour, which is rich in carbohydrate con-tent, as a raw material to produce bioethanol. To obtain the maximum ethanol concentration, several parameters had been studied, such as: the concentration of α-amylase and β-amylase in liquefaction and sac-charification processes, respectively, the type of S. cerevisiae enzyme (pure, dry, wet and instant) and weight of Diammonium phosphate (DAP) as a nutrient for S. cerevisiae in fermentation. The result shows that the highest reducing sugar content (12.5%) was achieved when 3.2 ml α-amylase/kg flour and 6.4 ml β-amylase/kg flour were used during liquefaction and saccharification processes. Since the concentration of α- and β-amylase increased, the reducing sugar obtained also increased. The higher sugar content resulted the higher the ethanol concentration in the fermentation broth. Furthermore, the highest concentration of ethanol (9 %v/v) was obtained at 72 h fermentation using the dry S. cerevisiae, at 3.2 ml and 6.4 ml /kg flour of α-amylase and β-amylase enzymes, respectively. From the study of the effect of S. cerevisiae type, it was shown that dry S. cereviseae produced the highest ethanol concentration 10.2% (v/v) at 72 h fermentation. The DAP was used as a nitrogen supply required by S. cerevisiae to growth and as a results can increase the ethanol concentration. The addition of DAP in the fermentation proved that 8.45% (v/v) of ethanol was obtained. This result shows that the proposed tuber flour has the potential a raw material for bioethanol production. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)